Characterization of multispecies microbial communities at beef and pork processing plants and their impact on pathogen stress tolerance - Wang, Rong; Chitlapilly Dass, Sapna; Palanisamy, Vignesh; Zhou, You; Katz, Tatum; Bosilevac, Joseph M. (Frontiers in Microbiology, 2025)
IntroductionE. coli O157: H7 and Salmonella enterica are major foodborne pathogens. Biofilm formation may potentially contribute to product contamination by these pathogens at meat processing facilities. Further, pathogen stress tolerance may vary significantly due to the interactions with the multispecies microbial community at meat plants, which may be affected by processing activity, animal species, and the local selective pressure caused by sanitization practices.MethodsWe characterized natural microorganisms collected from floor drains at various areas at three beef plants and two pork plants and analyzed their impact on pathogen sanitizer tolerance.ResultsThe pathogen strains were able to integrate efficiently into the multispecies community attached on contact surfaces even under low temperatures (7°C and 15°C) commonly seen in processing facilities. Cell density of the adhered S. enterica (4.9 to 6.3 log10 CFU/chip) was higher than E. coli O157: H7 (3.2–5.2 log10 CFU/chip). Contact surface materials and meat plant types did not affect surface attachment of either pathogen species. A multi-component sanitizer exhibited high efficiency that reduced the adhered pathogen cells in most samples to a non-enumerable level. However, overall higher survival and post-sanitization recovery of pathogen cells were observed in the treated pork plant samples than those in the beef plant samples. Scanning electron microscope analysis showed that the contact surface topography may impact the morphology of the attached microcolonies and bacterial tolerance. Metagenomic analysis of the multispecies bacterial communities showed that Pseudomonadaceae, Halomonadaceae and Enterobacteriaceae were the three most abundant families across all samples. No significant difference in genus compositions between the beef and pork plants or among the drain areas was observed. However, variations in the percentages of species’ relative abundance were observed among the samples.DiscussionThe multispecies microbial community at the processing plants and the resulting interspecies interactions could influence the tolerance level of the pathogens integrated into the community. Therefore, research reports on sanitization processes and the resulting pathogen inactivation and prevalence prevention that are described for the different types of processing facilities should be analyzed on a case-to-case basis.